Intervenções do terapeuta no processo de psicoterapia psicodinâmica de uma criança com sintomas externalizantes - Rosa, Catiane Pinheiro da (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation aimed at analyzing the process of psychodynamic psychotherapy of a child with externalizing symptoms, especially the interventions adopted. At first, a narrative review of the literature on the psychodynamic psychotherapy of children with externalizing symptoms was carried out, in order to identify the contributions of this modality of psychotherapy. Secondly, the therapeutic process of a child with externalizing symptoms was analyzed, in an empirical study, identifying the main interventions of the therapist. A longitudinal, descriptive research design was carried out, adopting the systematic case study procedure. The study’s participants were a child with externalizing symptoms, and his therapist. The Child Psychotherapy Q-Set (CPQ) procedure and the therapist's report on her perceptions about the child and the treatment were used. It was found that psychodynamic psychotherapy with children with externalizing symptoms may require the use of supportive and expressive interventions, as well as a technical flexibility, integrating different theoretical approaches. The empathic and affectively engaged posture of the therapist may also be important for treatment outcome.
Keywords: Psicoterapia psicodinâmica; Psicoterapia com crianças; Sintomas externalizantes; Pesquisa de processo; Psychodynamic psychotherapy; Psychotherapy with children; Externalizing symptoms; Process research; ACCNPQ::Ciências Humanas::Psicologia